Effects of chest physiotherapy and aerobic exercise training on physical fitness in young children with cystic fibrosis - Elbasan Bulent; Tunali Nur; Duzgun Irem; Ozcelik Ugur (BMC, 2012)
Abstract Background Cystic fibrosis is a multisystem disease where the main problems are existing in the respiratory system. Aerobic exercise programs are effective in increasing physical fitness and muscle endurance in addition to chest physiotherapy. Objective The aim of this study was to evaluate the effects of chest physiotherapy and aerobic exercise training on physical fitness in young children with cystic fibrosis. Methods Sixteen patients with cystic fibrosis, between the ages 5-13 years, were included in this study. All children were assessed at the beginning and at the end of 6 week of the training. Modified Bruce protocol was used for assessing the cardiovascular endurance. The sit-up test was used to evaluate the dynamic endurance of abdominal muscles, standing long jump was used to test power, sit and reach, trunk lateral flexion, trunk hyperextension, trunk rotation and forward bending tests were used to assess flexibility, 20 m shuttle run test and 10-step stair climbing tests were used to assess power and agility. All patients received chest physiotherapy and aerobic training, three days a week for six weeks. Active cycle of breathing technique and aerobic exercise training program on a treadmill were applied. Results By evaluating the results of the training, positive progressions in all parameters except 20 m shuttle run and 10 stairs climbing tests were observed (p < 0.05). Active cycle of breathing techniques were used together with exercise training in clinically stable cystic fibrosis patients increases thoracic mobility (p < 0.05) and the physical fitness parameters such as muscle endurance, strength and speed (p < 0.05). Comparison of the results in sit and reach and forward bending tests were not significant (p > 0.05). Conclusion It is thought that in addition to medical approaches to the systems affected, the active cycle of breathing techniques along with aerobic training helps to enhance the aerobic performance, thoracic mobility and improves physical fitness in children with cystic fibrosis.